Baduanjin exercise improves functional capacity and cardiovascular function in older adults with cardiovascular diseases: a systematic review and meta-analysis - Hu, Xingyu; Li, Yiran; Jiang, Haiyun; Luo, Zhihao; Zengqing; Zou, Jihua; Zheng, Xiaoyan (Frontiers in Cardiovascular Medicine, 2025)
BackgroundBased on clinical observations and expert recommendations, Baduanjin exercise has demonstrated a positive impact on maintaining and enhancing cardiovascular function. Despite clinical observations of Baduanjin's cardiovascular benefits, systematic evidence for older adults remains limited. Moreover, the effects of Baduanjin exercise on functional capacity in older adults with cardiovascular diseases have not been adequately investigated. Therefore, we conducted a systematic review and meta-analysis to evaluate the overall efficacy and effectiveness of Baduanjin exercise on functional capacity and cardiovascular function in older adults with cardiovascular diseases.MethodsWe conducted a systematic review and meta-analysis, searching related trials through March 7, 2025, across six databases: PubMed, Web of Science, Cochrane Library, China National Knowledge Infrastructure, Wanfang Data, and China Science Journal Database (VIP). Methodological quality was assessed using the Cochrane Risk of Bias Tool, and a meta-analysis of comparative effects was performed using Review Manager v.5.3 software.ResultsA total of 26 randomized controlled trials involving 2,080 participants were included in this meta-analysis. The results indicate that Baduanjin exercise significantly enhances functional capacity as measured by 6MWT compared to the control group (MD: 41.75, 95% CI: 33.08–50.42, p < 0.00001, I2 = 85%), and improves cardiovascular health markers including LVEF (MD: 5.04, 95% CI: 3.40–6.68, p < 0.00001, I2 = 82%). In dose-subgroup analysis, moderate exercise intensity (30–60 min per time) significantly improved cardiovascular function compared with those of the control group (MD: 56.36, 95% CI: 41.49–71.24, p < 0.00001, I2 = 92%). The secondary outcomes also demonstrated benefits in cardiac remodeling indices, including reductions LVESD (MD: −1. 67, 95% CI: −2.76 to −0.59, p = 0.002, I2 = 95%), LVDD (MD: −2.38, 95% CI: −3.59 to −1.17, p = 0.0001, I2 = 93%). In addition, Baduanjin exercise improved blood biomarkers such as NT-proBNP (MD: −183.83, 95% CI: −309.83 to −57.83, p < 0.00001, I2 = 82%) and NO (MD: 3.54, 95% CI: 1.74–5.34, p = 0.0001, I2 = 0%). What's more, it also decreased MLHFQ (MD: −7.00, 95% CI: −9.54 to −4.45, p = 0.0003, I2 = 79%).ConclusionsModerate-intensity Baduanjin (30–60 min/session) significantly improved 6MWT distance and cardiac function parameters by LVEF, LVESD, and LVDD, etc.Systematic Review Registrationidentifier, PROSPERO registration number: (CRD42023477008).